Pulmonary Disorders and Therapy (Neuroscience and Respiration ;, 2018)
The aim of this book is to present articles that are stimulating to read and inform readers with the most up-to-date clinical research. The articles incorporate the latest developments on a variety of topics in pulmonary medicine, therapy, and related mutlisystem disorders with varied manifestations. Emphasis is given to air quality and lung health, therapeutic management of airway reactivity and cough sensitivity linked to mucous clearance ability, ventilatory and cellular effects of hypoxia, influenza epidemics and persistently dismal vaccination coverage rate, disorders of mixed provenance and genetic background affecting lung parenchyma such as cystic fibrosis or Langerhans cell histiocytosis, and others. New diagnostic strategies and therapeutic management will hopefully serve to enhance the way patient care is delivered and thus clinical outcomes. Being a blend of medical research and practice the book addresses the needs of respiratory scientists and physicians, and allied health professionals.